2019
DOI: 10.1002/smll.201900730
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Assisted Growth of Patterned Perovskite Films for Sensitive Light Detector and Optical Image Sensor Application

Abstract: Controlled growth of high‐quality patterned perovskite films on a large scale is essentially required for the application of this class of materials in functional integrated devices and systems. Herein, graphene‐assisted hydrophilic–hydrophobic surface‐induced growth of Cs‐doped FAPbI3 perovskite films with well‐patterned shapes by a one‐step spin‐coating process is developed. Such a facile fabrication technique is compatible with a range of spin‐coated perovskite materials, perovskite manufacturing processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…The vacuum filtration method is also one of the solution processing methods along with the layer by layer deposition, Langmuir-Blodgett, selfassembly process, and very common spin coating method. [19] After extensive studies over these methods, the restacking of the graphene was again identified and as an improvement a different set of synthesis methods like template-assisted synthesis or graphene itself being a template, [20] additives based synthesis like spacers and crumpling of the sheets was reported. Among these, crumpling of graphene could play a role in changing their electronic properties.…”
Section: Freestanding/self-standing Graphene-based Electrode Materialsmentioning
confidence: 99%
“…The vacuum filtration method is also one of the solution processing methods along with the layer by layer deposition, Langmuir-Blodgett, selfassembly process, and very common spin coating method. [19] After extensive studies over these methods, the restacking of the graphene was again identified and as an improvement a different set of synthesis methods like template-assisted synthesis or graphene itself being a template, [20] additives based synthesis like spacers and crumpling of the sheets was reported. Among these, crumpling of graphene could play a role in changing their electronic properties.…”
Section: Freestanding/self-standing Graphene-based Electrode Materialsmentioning
confidence: 99%
“…Photodetectors (PDs), which transduce the optical signal into electric information, are one of the key semiconductor devices in many fields, such as optical image sensors, environmental surveillance, electrocommunication and remote sensing technology, etc. [1][2][3][4]. Three kinds of devices, i.e., photodiodes, photoconductors, and photo-FETs (field-effect transistors), are commonly adopted to detect optical signals.…”
Section: Introductionmentioning
confidence: 99%
“…Patterned template‐assisted crystallization of MHPs can create high‐quality nano/microcrystals with perfect surface and homogeneous crystal size. The patterned templates are usually composed of silicon, [ 27,30–33 ] silicon oxide, [ 34 ] alumina, [ 21,35–37 ] 2D materials, [ 38–40 ] and polymer [ 13,26,41–49 ] by the means of photolithography, direct laser writing, focused‐ion‐beam etching, or electron‐beam etching. The perovskite precursor solution is usually dropped on the hydrophilic substrates and confined by hydrophobic patterned molds to create crystal seeds and grow ordered crystal arrays.…”
Section: Perovskite Patterning Technologiesmentioning
confidence: 99%